Inquiry on the sun exposition in beach workers - Patrícia Froes Meyer; Rodrigo Marcel Valentim da Silva; Maria Goretti Freire de Carvalho; Monisa Martins Nóbrega; Amanda Spínola Barreto; Felipe de Sales Aires; Arilson Gois Gomes de Brito Oliveira; Efigênia Maria Nogueira da Silva; Evangelline Feitosa Cleomenes da Cruz Daams; Juliana Melo Souza; Marina Oliveira Menezes; Joaquina Elizete Cardoso da Silva (Universidade de Fortaleza, 2012)
Objective: To investigate the habits of photoexposition and photoprotection among beach workers in Natal-RN, Brazil. Methods: It is a descriptive observational epidemiological study of transverse type, with random sample consisting in 102 workers of Ponta NegraBeach, evaluated through a questionnaire of the Ministry of Health (DAS UV). Results: It was noted that 56% (n=57) of workers remain submitted to sun exposure for an average of 6 hours or more per day. It was found that approximately 24% (n=24) of respondents do notuse sun protection. Workers showed a low educational level, since 55% (n=56) had only attended elementary school, whether graduated or not, and average monthly income was below two minimum wages for 69.96% of volunteers. Conclusion: This assessment revealed that workers of Ponta Negra Beach, Natal-RN, are highly exposed to ultraviolet radiation during their professional activities, without proper photoprotection of skin.